The Evaluation of Endoscopic Balloon Dilation Treatment for Benign Gastric Outlet Obstruction - Javad Shokri-Shirvani; Alireza Arefzadeh; Hosein Foroutan; Hadi Ghofrani; Seyed Amir Mirbagheri (Acta Medica Iranica, 2009)
Balloon dilatation of stricture is one of the new treatment methods among patients with gastric outlet obstruction (GOO). However, the prevalence and underlying etiologies of GOO in various populations are different. The goal of the present study was to determine the effectiveness of endoscopic balloon dilatation and factors that would affect its success rate patients with benign etiology for GOO. Forty-five patients with the symptoms of benign GOO were randomly selected. Gastric outlet was delineated using double channel videoendoscopy. The information of initial balloon dilation was collected from recorded files. Balloon dilatation was repeated during the mean follow up of 9.9 ± 5.8 months. The severity of gastric pain was measured immediately before balloon dilatation and one month after procedure and was rated on a 10 cm visual analogue scale. The mean age of patients was 43.7 ± 18.1 years and 86.7% of them were men. Furthermore, 71.1% were H pylori positive. Response rate to endoscopic balloon dilatation was 80% and 8 patients underwent surgical resection. Weight loss was more frequent in non-responding group. The pain severity was significantly reduced more in responding subjects. No meaningful relationships were found between the responses to balloon dilatation and positive H pylori and cigarette smoking. Endoscopic balloon dilation is safe and effective for most patients with benign gastric outlet obstruction and has favorable long-term outcome.